The Voice System Of Papuan Malay: A Typological Study - Karubaba, Sara Yulita (Universitas Papua, 2017)
Papuan Malay is an Austronesian language spoken in the two provinces constituting Papua. Papuan Malay has four varieties. The Serui Malay variety is the main point of the discussion. I will show that the voice system of this variety displays two main levels of linguistic aspect: Â (1) Semantic argument level and (2) syntactical function. Both exhibit various patterns in active, passive and causative sentences. Among these are constructions of the type âX:S;Y: DOâ, i.e. the first semantic (macro) role X (Actor) is mapped onto grammatical relation of the Subject, while the second semantic (macro) role Y (undergoer) is mapped onto the grammatical relation of Direct Object. Particularly, an active sentence in this variety displays Semantic argument level (roles), and Syntactical function (S, O) in transitive sentences.There are three ways to construct passivity: (1) promotion of the object to the subject position, i.e. the object of the active sentence is promoted to be the subject of the passive sentence; (2) passive sentences; either the default agentless use of passive; or the optional, less common construction of mentioning the agent in an oblique phrase headed by dari âfromâ, which may also occur in transitive sentences. (3), causative transitive ; i.e. the causer takes the Subject position, and if the embedded verb is intransitive, transitive, or bitransitive, the causee appears as Direct Object, Indirect Object Object or Oblique Object.